MiR-138 Acts as a Tumor Suppressor by Targeting EZH2 and Enhances Cisplatin-Induced Apoptosis in Osteosarcoma Cells. - Ziqiang Zhu; Jinshan Tang; Jianqiang Wang; Gang Duan; Lei Zhou; Xiaoqing Zhou (PLoS ONE, 2016)
Chemotherapeutic insensitivity remains a major obstacle to treating osteosarcoma effectively. Recently, increasing evidence has suggested that microRNAs (miRNAs) are involved in drug resistance. However, the effect of miR-138 on cisplatin chemoresistance in osteosarcoma has not been reported. We used real-time PCR to detect the expression of mature miR-138 in osteosarcoma tissues and cell lines. Cell proliferation, invasion, and migration assays were used to observe changes to the osteosarcoma malignant phenotype. MiR-138 was downregulated in osteosarcoma tissues and cell lines, and miR-138 overexpression negatively regulated osteosarcoma cell proliferation, migration, and invasion. We also verified that EZH2 is a direct target of miR-138. Furthermore, enhancing EZH2 expression reduced the inhibitory effects of miR-138 on osteosarcoma. Proliferation, apoptosis assays and caspase-3 activity assay confirmed that elevated miR-138 expression enhanced osteosarcoma cell chemosensitivity to cisplatin by targeting EZH2. In conclusion, the present study demonstrates that miR-138 acts as a tumor suppressor by enhancing osteosarcoma cell chemosensitivity and supports its potential application for treating osteosarcoma in the future.